Determinants of worldwide diffusion of GlobalGAP certification - Amjad Masood; Bernhard Brümmer (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2014)
GlobalGAP is an important private standard in food sector. However, geographic diffusion of GlobalGAP is uneven across the world. We use a panel from 2008 to 2012 for 170 FAO member countries to analyze GlobalGAP diffusion in the agricultural sector as a whole as well as in the crops subsector. So far, studies on standards have been mostly dealing with farm level data and very few consider the case of macroeconomic determinants of diffusion only in case of public standards. We, on the other hand, consider the case of a private standard, namely GlobalGAP and estimate the macroeconomic determinants of GlobalGAP diffusion. For estimation, a Heckman two-stage model is applied using number of GlobalGAP certified producers as well as hectares of area harvested under GlobalGAP as dependent variables. We analyze the impact of network ties and historical relations among countries, and various macroeconomic conditions prevailing in courtiers on diffusion of certification. The study finds that diffusion is positively related common language, presence of auditing facility domestically and better infrastructure. We also find that countries with higher relative size of fruits and vegetables in the agriculture sector, and with more exports of fruits and vegetables to the EU states have higher coverage of GlobalGAP.
Keywords: 330; Standards; Food quality; Diffusion; Organizational innovation; GlobalGAP